The development of ECVET in Europe - (:unkn) unknown (Publications Office of the European Union, 2012)
"ECVET is now at a crossroads. It may well become the catalyst for innovation in education and training. But there is a risk that it will become lost among the many European education and training tools. What will most determine the success of ECVET is not just the relevant policy decisions, but their wide dissemination. The entire spectrum of education and training needs to understand how the ECVET contributes to learner mobility, transparency of qualifications, and greater parity between vocational and general education." This monitoring report describes the development of conditions and strategies for implementing the European credit system for vocational education and training (ECVET) in the Member States and the regions. It analyses current education and training systems in respect of their potential to support such implementation. (Hrsg., BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Europäisches Leistungspunktesystem; Lernergebnisorientierung; Europa